Pervasive plastisphere: First record of plastics in egagropiles (Posidonia spheroids). (October 2017) - Pietrelli, Loris; Di Gennaro, Alessia; Menegoni, Patrizia; Lecce, Francesca; Poeta, Gianluca; Acosta, Alicia T.R.; Battisti, Corrado; Iannilli, Valentina
Abstract: The ability of Posidonia oceanica spheroids (egagropiles, EG) to incorporate plastics was investigated along the central Italy coast. Plastics were found in the 52.84% of the egagropiles collected (n = 685). The more represented size of plastics has range within 1–1.5 cm, comparable to the size of natural fibres. Comparing plastics occurring both in EG and in surrounding sand, Polyethylene, Polyester and Nylon were the most abundant polymers in EG, while PSE, PE, PP and PET were the most represented in sand. In particular PE and PP were significantly more represented in sand, while PE, Nylon, Polyester and microfibers (as pills) were more represented in EG. Within plastics found in EG, 26.9% were microfibers as small pills (<1 cm), mainly composed of polyamide, polyester, cotton and PET mixing. These microfibers might be produced by discharges from washing machines and currently represents an emerging pollutant with widespread distribution in marine and freshwater ecosystems. Graphical abstract: Highlights: The ability of Posidonia egagropiles to incorporate plastics was investigated. Plastics were found in about 53% of egagropiles. 1–1.5 cm is the most represented size of plastics. Polyethylene and Nylon are the most common polymers. Abstract : First record of plastics in Posidonia egagropiles.